Coupled Thermomechanical Multiscale Modeling of Alumina Ceramics to Predict Thermally Induced Fractures Under Laser Heating. Issue 3 (5th December 2014) - Dong, Xiangyang; Shin, Yung C.
Abstract : This study is concerned with thermally induced fractures and failure of high weight percentage alumina ceramics. A 3D coupled thermomechanical multiscale model has been developed to simulate thermally induced fractures. In laser heating of alumina ceramics, the temperature and stress distributions have been predominantly correlated with the interfacial glass phase within alumina microstructure. A coupled thermomechanical analysis with traction–separation law has been implemented in the finite element framework as a cohesive zone model (CZM). The alumina grains are modeled as thermomechanical continuum elements separated by CZM. A thermal and mechanical analysis has been conducted using Molecular Dynamics methods to obtain the thermal conductivities and parameterize traction–separation laws for the interface of alumina ceramics at different temperatures. The coupled thermal‐mechanical analysis achieved through a finite element model in Abaqus is compared with experimental results in laser‐heating tests. The model is successful in predicting temperature distributions and thermal fractures, which could help assist in selecting proper conditions in alumina applications and fabrication processes.